Educational interventions and communication strategies to improve HPV immunization uptake: a systematic literature review - D’Ambrosio, Floriana; Sezzatini, Romina; Bucciardini, Raffaella; Maida, Ada; Nisticò, Anna; De Vito, Elisabetta; Ricciardi, Walter; Boccia, Stefania; Calabrò, Giovanna Elisa (Frontiers in Public Health, 2025)
IntroductionHuman Papillomavirus (HPV) infection represents a global health concern, causing approximately 627,000 cancer cases in women and 69,400 in men annually. Despite the proven value of HPV vaccines, disparities in vaccination coverage persist worldwide, highlighting the need for coordinated efforts to address vaccine acceptance and promote equitable access. To tackle this global challenge and align with the World Health Organization’s (WHO) strategy to eliminate cervical cancer by 2030, implementing effective interventions to enhance knowledge within target populations is crucial to increasing vaccination uptake. This systematic review aimed to explore educational interventions and communication strategies employed by healthcare professionals (HCPs) to improve HPV vaccine coverage.MethodsA systematic literature review was conducted by querying three databases from July 2006 to July 2025. Eligible studies were systematic literature reviews (SLRs) and primary studies not included in SLRs, focused on international educational and communication strategies implemented by HCPs targeting the WHO-recommended populations for HPV vaccination, as well as parents and other influential stakeholders involved in vaccination decision-making.ResultsA total of 17 studies were included, of which 6 SLRs and 11 primary studies, with 71% (12/17) focusing on educational interventions and 29% (5/17) on communication strategies. HPV vaccine-eligible individuals were targeted in 41% (7/17) of studies, while parents and other stakeholders in 59% (10/17). Narrative videos were the most common employed strategy (53%, 9/17), followed by written informative materials (35%, 6/17), social media (29%, 5/17), and person-to-person solicitation (23%, 4/17).ConclusionThe findings underscore the importance of tailored communication strategies to raise awareness and effectively engage diverse populations. Identifying strengths and gaps in current approaches is essential for creating evidence-based interventions that not only promote reliable information but also inform effective public health policies. Aligning these efforts with the WHO’s call to action is crucial to maximizing the whole value of vaccination, reducing the global burden of HPV-related diseases, and advancing toward cervical cancer elimination by 2030.